Continuity (Solution 2)
Continuity (Solution 2)
Continuity (Solution 2)
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[129]
5. Observing the options, let us verify the continuity of f (I ) = 0
f (x ) at x = 0 and 1: f (I + ) = 0
f (0 − ) = lim [0 − h ]2 − (0 − h )2
h →0
[ ] Hence f is discontinuous at x = 0
If I > 0 then:
= (− 1)2 − 0 = 1 f (I − ) = 2 − 2I , f (I ) = 0 , f (I + ) = 0
Hence f can be continuous if 2 − 2I = 0 ⇒ I = 1 . Hence
f (0 + ) = lim [0 + h ]2 − (0 + h )2
h →0
[ ] f is continuous at x = 1 .
Hence 1 is the only integer at which f (x ) is continuous.
= 02 − 0 = 0
( )
f (x ) = x 2 − 1 | x 2 − 3x + 2 | + cos( x )
[ ]
6.
f (0 ) = [0] − 0
2 2
=0 ⇒ f (x ) = (x − 1)(x + 1) | (x − 1)(x − 2) | + cos x
Hence f is discontinuous at x = 0. ⇒ f (x ) = (x + 1)(x − 1) | (x − 1) | | (x − 2 ) | + cos x
h →0
[
f (1 − ) = lim [1 − h ]2 − (1 − h )2
] Clearly the function y = (x + 1)(x − 1) | (x − 1) | | (x − 2 ) | is
not differentiable only at x = 2 . Also y = cos x is
= 02 − 0 = 0 differentiable everywhere. Hence the given summation
f (1 + ) = lim [1 + h ]2 − (1 + h )2
h →0
[ ] 7.
is not differentiable only at x = 2 .
Options a, b, d are wrong. For example consider the
(D)
following graph:
= 12 − 1 = 0
[ ]
f (1) = [1]2 − 12 = 1 − 1 = 0
Hence f is continuous at x = 1 . Hence from the nature
of options it follows that f is discontinuous at all
integers except at x = 1 .
NOTE: f (I − h ) = lim [I − h ]2 − (I − h )2
[ ]
h →0 Clearly range of f (x ) and range of f (x ) are not same.
[
= lim (I − 1)2 − I 2 − 2Ih + h 2
h →0
] Also graph of f (x ) is one-one type while graph of f (x )
is many-one type. Again f (x ) is differentiable in [a , b]
= (I − 1)2 − (I − 1) if I > 0
2
while f (x ) is not differentiable at x = c due to sharp
and
turning. However if f (x ) is continuous then f (x ) must
(I − 1)2 − (I ) if I ≤ 0
2
be continuous. (c)
= 2 − 2I if I > 0
and 8. P(x ) = a 0 + a 1 x + a 2 x + ... + a n x
2 n
1− 2I if I ≤ 0 ⇒ P / (x ) = a 1 + 2a 2 x + 3a 3 x 2 + ... + na n x n −1
f (I + h ) = lim [I + h ]2 − (I + h )2
h →0
[ ] ⇒ P / (1) = a 1 + 2a 2 + 3a 3 + ... + na n
P(x ) ≤ e x −1 − 1
[
= lim I 2 − I 2 + 2Ih + h 2
h →0
] ∀x ≥ 0 …(i)
⇒ P(1) ≤ e 0 − 1
= I 2 − I 2 if I ≥ 0
and ⇒ P(1) ≤ 0 ⇒ P(1) = 0 ⇒ P(1) = 0
2
( 2
I − I − 1 if I < 0 ) Again substituting (1 + ∆x ) in place of x in (i):
= 0 if I ≥ 0 P(1 + ∆x ) ≤ e ∆x − 1
and
1 if I < 0 ⇒ P(1 + ∆x ) − P(1) ≤ e ∆x − 1 , (∵ P(1) = 0 )
[ ]
f (I ) = [I]2 − I 2 =0
P(1 + ∆x ) − P(1) e ∆x − 1
Hence if I < 0 then: ⇒ ≤
∆x ∆x
f (I − h ) = 1 − 2I , f (I ) = 0 , f (I + h ) = 1
Hence f can not be continuous at x = I when I < 0 . P(1 + ∆x ) − P(1) e ∆x − 1
⇒ lim ≤ lim
If I = 0 then: ∆x →0 ∆x ∆x →0 ∆x
f (I − ) = 1 − 2I = 1 − 2 × 0 = 1
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[130]
⇒ P (1) ≤ ln e ⇒ P (1) ≤ 1
/ / − sin x + x
g (x ) = sin ( | x | )− | x |=
if x < 0
sin x − x if x ≥ 0
⇒ a 1 + 2a 2 + 3a 3 + ... + na n ≤ 1
Hence g (0 − ) = 0 and g (0 + ) = 0 .
/ /
f / (k − ) = lim
f (k − h ) − f (k ) [k − h ]sin (π(k − h )) − 0 (d)
9.
−h
=
−h Hence g(x ) = sin ( | x | )− | x | is differentiable at x = 0.
h →0
12. f (x ) − f (α ) = (x − α )g(x ) ∀ x ∈ R
(k − 1)(− 1)k +1 sin (πh )
= lim f (x ) − f (α )
h →0 + −h ⇒ g(x ) = ∀x ∈ R − α
x−α
sin (πh )
= (k − 1)(− 1)k lim π Also since g(x ) is a continuous function therefore
h →0 πh
g(α ) = lim g(x ) = a fixed and finite quantity.
= (k − 1)(− 1)k (1)π = (k − 1)(− 1)k π (a) x →α
⇒ g(α ) = lim g(x ) = lim g(x ) = fixed and finite
10. The graphs of y = x and y = x 3 are given in the x →α + x →α −
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[131]
Clearly f is not continuous at x = −1 and 1. Hence ⇒ 1 = b + 1 = b + 1 and (a − 1) + b = b = b and
2
1 1+ b = 1+ b = 1+ b
− if x < −1
2 ⇒ b = 0 & a = 1.
φ if x = −1 Again for these values of a & b
1 g(f (x ) ) = x + 2 , x < −1
f / (x ) = if − 1 < x < 1
2
1 + x = x2 , −1 ≤ x < 1.
φ if x = 1
= (x − 2) , x ≥ 1.
2
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[132]
e ah / 2 − 1 e ah / 2 − 1 a a 19. f (x − y ) = f (x ) . g(y ) − f (y ) . g(x ) ∀ x, y ∈R
lim f (x ) = lim = lim . =
x →0 + h →0 h h →0 ah / 2 2 2 ⇒ f (x − x ) = f (x ) . g(x ) − f (x ). g(x ) , putting y = x
c−h −1 c ⇒ f (0 ) = 0
lim f (x ) = lim b sin −1 = b sin
x →0 − h →0 2 2 Substituting y = 0 :
1 f (x − 0 ) = f (x ). g(0) − f (0) . g(x ) ∀ x∈R
f (0 ) = (given).
2 ⇒ f (x ) = f (x ) . g(0) ∀ x ∈R, (∵ f (0 ) = 0)
c a 1 ⇒ {1 − g(0 )}f (x ) = 0 ∀ x ∈R
∴ b sin −1 = = . Hence a = 1.
2 2 2 ⇒ f (x ) = 0 ∀ x ∈R or g(0 ) = 1 .
Also f (x ) is differentiable at x = 0. (i) Let f (x ) = 0 ∀ x∈R. Hence
e h / 2 −1 1 g(x − y ) = g(x ).g(y ) + f (x ).f (y )
−
f / (0 + ) = lim h 2 ⇒ g(x − y ) = g(x ).g(y )
h →0 h ⇒ g(x − x ) = g(x ).g(x ) , putting y = x
2e h / 2 − 2 − h 0
= lim
2
, form ⇒ g(0 ) = g 2 (x ) ⇒ g(x ) = constant
h →0 2h 0
1 ⇒ g / (x ) = 0 ⇒ g / (0) = 0 .
2e h / 2 . − 1 (ii) Let g(0 ) = 1. Hence
2 eh / 2 −1 1
= lim = lim =
h →0 4h h →0 8(h / 2 ) 8 f (0 + h ) − f (0 )
f / (0 + ) = lim
c−h 1 h →0 h
b sin −1 −
2 2 0 f (0 − (− h )) − f (0 )
f (0 − ) = lim
/
, form = lim
h →0 −h 0 h →0 h
1 f (0 ).g(− h ) − f (− h ).g(0 ) − f (0)
b×− = lim
h →0 h
2
−0 0 − f (− h ).1 − 0 − f (− h )
c−h
2 = lim = lim
1− h →0 h h →0 h
2 b f (0 − h ) − f (0)
= lim = = lim , (∵ f (0 ) = 0)
h →0 −1 4 − c2 h →0 −h
1 b = f / (0 − )
Hence = ⇒ 64b 2 = 4 − c 2 .
8 4 − c2 Hence f (x ) is differentiable at x = 0.
g(x − y ) = g(x ).g(y ) + f (x ).f (y ) ∀ x, y ∈R
18. f (x 1 ) − f (x 2 ) ≤ (x 1 − x 2 )2 ∀ x 1 , x 2 ∈R
⇒ g(x − x ) = g(x ).g(x ) + f (x ).f (x ) , putting y = x
⇒ f (x 1 ) − f (x 2 ) ≤ x 1 − x 2
2
∀ x 1 , x 2 ∈R
⇒ g(0 ) = g 2 (x ) + f 2 (x )
⇒ f (x + ∆x ) − f (x ) ≤ (x + ∆x ) − x
2
∀ x∈R Differentiating both sides with respect to x:
f (x + ∆x ) − f (x ) (∆x )2 ⇒ 0 = 2g(x ). g / (x ) + 2f (x ).f / (x ) ∀ x ∈R
⇒ ≤ ∀ x∈R
∆x ∆x ⇒ 0 = 2g(0) . g / (0) + 2f (0) . f / (0)
⇒ lim
f (x + ∆x ) − f (x )
≤ lim ∆x ∀ x∈R
(
⇒ 0 = 2g(0 ). g / (0) + 0 , ∵ f (0) = 0 & f / (0 ) is finite )
∆x →0 ∆x ∆x →0 ⇒ g / (0) = 0
⇒ f / (x ) ≤ 0 ∀ x∈R ⇒ f / (x ) = 0 ∀ x∈R From (i) and (ii) it follows that g / (0) = 0 .
⇒ f (x ) = constant x x
20. F(x ) = f 2 + g 2
2 2
x x 1 x x 1
⇒ F / (x ) = 2f . f / . + 2g g / .
2 2 2 2 2 2
x x x x
⇒ F / (x ) = f . f / + g . g / …(i)
Since f (1) = 2 therefore f (x ) = 2 ∀ x∈R.
2 2 2 2
Since a straight line is tangent to itself therefore the But g (x ) = f / (x )
equation of the tangent is y − 2 = 0 .
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[133]
x x hn
⇒ g = f / …(ii)
2
x
2
x
⇒ lim
(
h →0 cos m h − 1 ) = −1
dg df / nh n −1
⇒
2
dx
=
2
dx
⇒ lim
(
h →0 cos m h − 1 ) = −1
x 1 x 1
⇒ g / . = f // . nh n −1
⇒ lim = −1
2 2 2 2 h →0 m(cosh )m −1 (− sinh )
x x
⇒ g / = f // …(iii) − nh n −1 1
2 2 ⇒ lim . lim = −1
h →0 sinh h →0 (cosh )m −1
Also f / (x ) = −f (x ) m .h
h
⇒ f // (x ) = −f / (x )
x x
…(iv)
⇒ lim
− n n −2
h →0 m
h ( = −1 )
⇒ f // − f / …(v)
2 2 Clearly if n < 2 then the limit does not exist. If n > 2
x x −n n
From (ii) & (iii) substituting values of g & g / then the limit is . Hence n = 2 and − − 1
2 2 m m
in (i): ⇒ n = 2&n = m . (c)
x x x x 22. lim (g (x ) cot x − g (0 ). cos ecx )
F / (x ) = f . f / + g . g / x →0
2 2 2 2
g(x ) cos x − g (0 ) 0
x x x x = lim , form
⇒ F / (x ) = f . f / + f / . f // x →0 sin x 0
2 2
2 2
g / (x ) cos x − (sin x )g (x )
x x x x = lim
⇒ F / (x ) = f . f / + f / . − f / x →0 cos x
2 2 2 2
g / (0 ) cos 0 − 0 × g (0 )
x x
∵ f // = −f / = = g / (0 ) = 0
1
2 2
f (x ) = g (x ) sin x
x x x x
⇒ F / (x ) = − f / . f / + f / . − f / ⇒ f / (x ) = g(x ) cos x + sin x g / (x ) …(i)
2 2
2 2
(∵ f (x ) = −f / (x )) ⇒ f // (x ) = g / (x ) cos x + (− sin x )g(x ) + sin xg // (x )
⇒ lim
(1 + h − 1)n = −1
cause for the given limit to be equal to f // (0) . (b)
h →0 log cos m (1 + h − 1) 23. g (x ) = log f (x ) …(i)
⇒ g (x + 1) = log f (x + 1)
hm
⇒ lim = −1 ⇒ g (x + 1) = log(xf (x ))
h →0 log cos m h
⇒ g (x + 1) = log x + log f (x ) …(ii)
hm From (i) & (ii):
⇒ lim
( (
h →0 log 1 + cos m h − 1 )
cos m h − 1
= −1
g (x + 1) − g (x ) = log x
(m
cos h − 1 ) ⇒ g / (x + 1) − g / (x ) =
1
x
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[134]
1 π
⇒ g // (x + 1) − g // (x ) = − …(iii) = lim (− h ) cos
x2 h→0 h
1 = 0 × a quantity oscillating between −1 to 1
Substituting x = N − = 0 × finite = 0
2
1 1 −1 π
⇒ g // N + − g // N − = h 2 cos
f (0 + h ) − f (0 ) h
f / (0 + ) = lim
2 2 2
1 = lim
N − h→0 h h→0 h
2
π
1 1 − 4 = lim h cos
⇒ g // N + − g // N − = …(iv) h→0 h
2 2 (2 N − 1)2
= 0 × a quantity oscillating between −1 to 1
Substituting N = 1,2,3,..., N − 1, N : = 0 × finite = 0
3 1 −4 Hence f (x ) is differentiable at x = 0 .
g // − g // =
2 2 12
To verify differentiability at x = 2 :
5 3 −4
g // − g // = 2 π
2 2 32 x cos , x ≠ 0
f (x ) = x
7 5 −4 0
g // − g // = , x=0
2 2 52
π
…………………………. Hence f (x ) = x 2 cos in neighborhood of x = 2 .
…………………………. x
1 3 −4 2 π
g // N − − g // N − =
2 2 (2 N − 3)2 x − cos x , 2 − h < x < 2
∴ f (x ) =
1 1
g // N + − g // N − =
−4 x 2 cos π , 2 ≤ x < 2 + h
2 2 (2 N − 1)2 x
π π
1 1
Adding : g // N + − g // − 2 x cos x − π sin x , 2 − h < x < 2
2 2
⇒ f / (x ) = φ ,x=2
1 1 1 1 π π
= −4 + + + ... + 2 x cos + π sin , 2< x < 2+h
12 32 5 2 ( − )2 x x
2 N 1
24. f (x ) is differentiable at x = 0 . Since f / (2 − ) = − π & f / (2 + ) = π therefore f / (2 ) = φ .
f (x + ∆x ) − f (x ) Hence f (x ) is differentiable at x = 0 but not derivable
∴ f / (x ) = lim
∆x →0 ∆x at x = 2. (b)
f (x ) + f (∆x ) − f (x ) f (∆x )
= lim = lim Alternative:
∆x → 0 ∆ x ∆ x → 0 ∆x
f (0) + f (∆x ) − f (0 ) To verify differentiability at x = 2 :
= lim π
∆x → 0 ∆x (2 − h )2 cos
f (0 + ∆x ) − f (0 ) f (2 − h ) − f (2) (2 − h )
= lim = f / (0) f / (2 − ) = lim = lim
∆x → 0 ∆ x h →0 −h h →0 −h
Hence if f (x ) is differentiable at x = 0 then f (x ) is (2 − h )2 cos π(2 − h )−1
= lim
differentiable everywhere & f / (x ) = f / (0) = a constant. h→0 −h
( )
So f is continuous everywhere. (b, c) −1
2 π (2 − h )2 cos π 2 −1 1 − h
x cos , x ≠ 0 2
25. f (x ) = x , x∈R = lim
0 , x=0 h→0 −h
To verify differentiability at x = 0 : (2 − h )2 cos π 1 + h
π 2 2
h 2 cos = lim
f (0 − h ) − f (0) h h →0 −h
f / (0 − ) = lim = lim
h→0 −h h →0 −h
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[135]
lim f (2 n + 1 − h ) = lim (a n + sin π(2 n + 1 − h )) = a n
(2 − h )2 cos π + πh h→0 h →0
2 4 lim f (2n + 1 + h ) = lim (b n + cos π(2n + h )) = b n + 1
= lim
h →0 − h h→0 h→0
Also f (2 n + 1) = a n .
(2 − h )2 − sin πh (2 − h )2 sin πh
4 4 ∴ a n = b n + 1 ⇒ a n − b n = 1.
= lim = lim
h →0 −h h →0 −h ∴ f (x ) is continuous for all x ∈ R if a n − b n = 1. (b)
( )
−1 h
= lim =0
(2 + h )2 cos π 2 −1 1 + h e2/ h
h →0
2
= lim Since f (0 − ) = f (0) = f (0 + ) = 0 therefore f (x ) is
h→0 h continuous at x = 0 .
(2 + h )2 cos π 1 − h To verify differentiability at x = 0 :
2 2 1 1
− +
= lim
h →0 h he h h −0 1
f / (0 + ) = lim = lim =0
h −0 2/h
(2 + h )2 cos π − πh
h →0 h →0 e
2 4 1 1
− −
= lim
h →0 h
f / (0 − ) = lim
(− h ) e h h −0
= lim e 0 = 1
(2 + h )2 sin πh h →0 (− h ) − 0 h →0
(2 + h )2 sin πh
= lim
4
= lim 4 Since f (0 + ) ≠ f / (0 − )
/
therefore f (x ) is not
h →0 h h →0 h differentiable at x = 0 . (b)
(2 + h )2 sin πh
4 = lim π (2 + h )2 = π 1 − tan x π
= lim
πh 4 2. f (x ) = , x≠
h→0 × h →0 4 4x − π 4
4 π 1 − tan x 0
∴ lim f (x ) = lim , form
Since f / (2 − ) ≠ f / (2 + ) therefore the function is not x →π / 4 x → π / 4 4 x − π 0
differentiable at x = 2 . (b) − sec 2 x
= lim
x → π / 4
a + sin πx , for x ∈ [2n,2n + 1] 4
26. f (x ) = n
b n + cos πx , for x ∈ (2n − 1, 2n ) =
− sec 2 π / 4
=−
1
For f (x ) to be continuous for all x, it must be 4 2
continuous at x = 2n & x = 2n + 1, ∀ n ∈ I. π π
Hence for f (x ) to be continuous in 0, , f must
For f (x ) to be continuous at x = 2n : 2 4
lim f (2 n − h ) = lim (b n + cos π(2 n − h )) = b n + 1 1
h →0 h →0 be − . (c)
2
lim f (2 n + h ) = lim (a n + sin π(2n + h )) = a n
h →0 h →0 3. f (x ) − f (y ) ≤ (x − y )2 ∀ x , y ∈R
Also f (2n ) = a n .
⇒ f (x ) − f (y ) ≤ x − y
2
∀ x , y ∈R
∴ a n = b n + 1 ⇒ a n − b n = 1.
⇒ f (x + ∆x ) − f (x ) ≤ (x + ∆x ) − x
2
For f (x ) to be continuous at x = 2n + 1 : ∀ x∈R
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[136]
f (x + ∆x ) − f (x ) (∆x ) 2 1 2 e 2 x − 1 − 2x
f (0) = lim − = lim
⇒
∆x
≤
∆x
∀ x∈R
x → 0 x e 2 x − 1 x → 0 x e 2 x − 1 ( )
f (x + ∆x ) − f (x ) e 2 x − 1 − 2x 1
⇒ lim ≤ lim ∆x ∀ x∈R = lim ×
∆x →0 ∆x ∆x →0 x →0 (x )(2x ) e 2x
−1
⇒ f /
(x ) ≤ 0 ∀ x∈R ⇒ f (x ) = 0 ∀ x∈R
/ 2x
e 2x − 1 − 2x 1
⇒ f / (x ) = 0 ∀ x∈R = lim
2
×
x →0 2x ln e
⇒ f (x ) = constant
e 2x − 1 − 2x 0
Since f (0 ) = 0 therefore f (x ) = 0 ∀ x∈R. = lim , form, apply L.H. Rule
x →0 2 0
Hence f (1) = 0 . (d) 2x
2x 2x
x 2e −2 e −1
, x≥0 = lim = lim = ln e = 1 . (d)
x 1 + x x →0 4x x →0 2x
4. f (x ) = =
1+ x x 1
, x<0 (x − 1) sin if x ≠ 1
1 − x 7. Let f (x ) = x −1
The only possible point at which f (x ) may not be 0 if x = 1
differentiable is x = 0 . − 1 1 1
⇒ f / (x ) = cos + sin if x ≠ 1
( )
Now f / 0 + = lim
h →0
f (0 + h ) − f (0)
h
(x − 1) x − 1
⇒ f / (0) = cos1 − sin 1
x −1
h
−0 Hence f (x ) is differentiable at x = 0 .
= lim 1 + h f (1 + h ) − f (1)
1
= lim =1
h →0 h h →0 1 + h f / (1 + ) = lim
h→0 h
−h
−0 1
/ ( )−
f 0 = lim
h →0
f (0 − h ) −
(− h )
f (0 ) = lim
h →0
1 − (− h)
−h
= lim
h sin − 0
h = lim sin
1
h →0 h h→ 0 h
1 = a quantity oscillating between −1 to 1.
= lim =1
h →0 1 + h Hence f / (1 + ) does not exist. Similarly f / (1 − ) does not
Since f 0 / ( ) = f (0 ) therefore f (x ) is differentiable at
+ / − exist. So the function is differentiable at x = 0 but not
x = 0 . Hence f (x ) is differentiable every where. (c) at x = 1 . (c)
f (x ) = x x
f (x ) = min{x + 1, x + 1}
8.
5.
min{x + 1, x + 1}, x ≥ 0 ⇒ f (x ) = − x 2 , if x < 0
⇒ f (x ) =
min{x + 1, − x + 1}, x < 0 = x2 , if x ≥ 0
Sketching graphs of y = x + 1 & y = − x + 1 : Also given g(x ) = sin x .
( )
∴ g(f (x )) = sin − x 2 , if x < 0
= sin (x 2 ) , if x ≥ 0
⇒ g(f (x )) = − sin (x 2 ) , if x < 0
= sin (x 2 ) , if x ≥ 0
= −2x cos(x 2 ) , if x < 0
d (g(f (x )))
⇒
dx
=0 , if x = 0
x + 1, x ≥ 0
From above graph f (x ) =
x + 1, x < 0
. = 2x cos x 2 ( )
, if x > 0
Clearly gof is differentiable at x = 0 and its derivative
Hence f (x ) = x + 1 ∀ x ∈ R , which is continuous and
differentiable ∀ x ∈ R . (c) is continuous at that point. Hence statement-1 is true.
1 2
6. For f (x ) = − to be continuous at x = 0 : Also
x e 2x − 1
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[137]
d 2 (g(f (x )))
dx 2
(
= − 4x 2 sin x 2 + 2 cos x 2 ) , if x < 0 2I − 1
= I × cos
2
π
=φ , if x = 0 = I×0 = 0
2(I − h ) − 1
( 2
= 4x sin x + 2 cos x 2
, if x > 0 2 ) lim f (I − h ) = lim [I − h ]cos
h→0 h→0 2
π
Hence gof is not twice differentiable at x = 0 . Hence
= lim [I − h ] × lim cos
2 (I − h) − 1
π
statement-2 is false. (c) h→0 h→0 2
2I − 1
= lim [I − h ] × cos π
sin (p + 1)x + sin x , x < 0 h→0 2
x = lim [I − h ] × 0 = 0
9. f (x ) = q ,x=0 h→0
Hence f (x ) is continuous for all x ∈ R . (a)
x + x2 − x
,x>0 11. f (x ) = x − 2 + x − 5 , x ∈ R
x3/ 2
⇒ f (x ) = (x − 2 ) − (x − 5), x ∈ (4 − h,4 + h ) ,where h → 0
h + h2 − h ⇒ f (x ) = 3 , x ∈ (4 − h,4 + h ), h → 0
lim f (x ) = lim f (0 + h ) = lim
x →0+ h →0 h→0 h3 / 2 ⇒ f / (x ) = 0 , ∀ x ∈ (4 − h,4 + h ), h → 0
1+ h −1
= lim ⇒ f / (4 ) = 0 is true.
h→0 h
( 1 + h − 1)( 1 + h + 1)
Hence statement I is true.
= lim Also y = x − 2 & y = x − 5 both being continuous
h→0 h ( 1 + h + 1) functions their summation is also continuous ∀ x ∈ R .
= lim
h Also, since (x − 2 ) ≥ 0 and (x − 5) ≤ 0 for all x ∈ [2,5]
(
h→0 h 1 + h + 1 ) therefore
1 1 f (x ) = (x − 2 ) − (x − 5) , ∀ x ∈ [2,5]
= lim
h→0 ( 1 + h + 1) = 2 ⇒ f (x ) = 3 , ∀ x ∈ [2,5]
lim f (x ) = lim f (0 − h ) ⇒ f (x ) is differentiable on [2, 5]
x →0− h →0
Again f (2 ) = f (5) = 3. Hence statement-2 is true. So by
sin (p + 1)(− h ) + sin (− h )
= lim , Rolle’s theorem it follows that there is at least one point
h→0 −h
in (2,5) where f / (x ) = 0 . But it does not mean the point
0
form, apply L.H. Rule is x = 4 . Hence statement-II is not correct explanation
0 for statement-I. (c)
= lim
(p + 1) cos(p + 1)h + cosh
12. Let f ( x ) = [ x ] + 1 − x , −1 ≤ x ≤ 3
h →0 1
Where [x] = greatest integer function.
= (p + 1) + 1 = (p + 2 )
For f to be continuous for x ∈ R it needs to continuous f is not continuous at x = 0,1, 2,3
at x = 0 . But in statement-2 f(x) is continuous at x = 3
1 3 1
∴ (p + 2 ) = q = ⇒ p = − , q = . (c) Hence, statement-1 is true and 2 is false. (a)
2 2 2
1
2x − 1 13. µ ( x ) = which is discontinuous at x = 1
10. f (x ) = [x ]cos π x −1
2 1 1
Since y = [x ] is discontinuous at every integer point f (u) = = ,
u + u − 2 ( u + 2 )( u − 1)
2
2x − 1
x = I and y = cos π is continuous every where Which is discontinuous at u = −2,1
2
therefore the only possible point of discontinuity is 1 1
x = I. When u = −2 , then == −2 ⇒ x =
x −1 2
2I − 1
Now f (I ) = [I ]cos π = I × 0 = 0 1
2 When u = 1 , then =1⇒ x = 2
2(I + h ) − 1 x −1
lim f (I + h ) = lim [I + h ]cos π
h→0 h→0 2
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[138]
Hence given composite function is discontinuous at 1 sin x
= ∵ lim = 1 (d)
1
three points, x = 1, and 2 . (b)
4 x →0 x
2
9 2
16. Given that f =
14. fog = f ( g ( x ) ) = f (1 − x ) 2 9
= −1 + 1 − x − 2 1 − cos 3x x2
lim f = lim
x →0 x2 x →0 1 − cos 3x
= −1 + − x − 1 = −1 + x + 1
9 2 4
Let fog = y x2 1 4 x .9
= lim = lim
x →0 2 sin 2 3x 2 x →0 sin 2 3x
∴ y = −1 + x + 1
2 2
−1 + x + 1, x ≥ 0
⇒y=
−1 − x + 1, x < 0
x, x ≥ 0
⇒y= 4 1
− x, x < 0 = lim
9 × 2 x →0 sin 2 3x
LHL at ( x = 0 ) = lim ( − x ) = 0 2
x →0 2
3x
RHL at ( x = 0 ) = lim ( x ) = 0 2
x →0
When x = 0, then y = 0
Hence, LHL at ( x = 0 ) = RHL at ( x = 0 )
lim 1
2 →0
sin x
= value of y at ( x = 0 ) = x lim = 1
9 3x x →0 x
sin 2
Hence y is continuous at x = 0 2
xlim
→0 3x 2
Clearly at all other point y continuous. Therefore, the set
of all points where fog is discontinuous is an empty set. 2
(d) 2 1 2
= ⋅ = (b)
2 + cos x − 1 9 1 9
15. Since f ( x ) = is continuous at x = π
( π − x )2 17. Let f ( x ) ≤ x 2 , ∀x ∈ R
∴ LHL = RHL = f ( π )
Now, at x = 0, f ( x ) ≤ 0 ⇒ f / ( 0 ) = 0
Let ( π − x ) = θ, θ → 0 when x → π
f ( h ) − f (0) f (h)
∴ f / ( 0 ) = lim = lim …(1)
2 − cos θ − 1 h →0 h −0 h →0 h
∴ lim
θ→0 θ2 f (x)
( 2 − cos θ ) − 1 1
Now,
h
≤ h (∵ f ( x ) ≤ x ) 2
= lim ×
θ→0 θ2 2 − cos θ + 1 f (h)
⇒−h ≤ ≤ h
1 − cos θ 1 h
= lim = . (∵ cos 0 = 1)
θ→0 θ2 2 f (h)
⇒ lim →0 …(2)
1 2 sin 2 θ / 2 2 2 sin 2 θ / 2 h →0 h
= lim = lim
2 θ→0 θ2 2 θ→0 θ2 (using sandwich Theorem)
.4
4 ∴ from (1) and (2), we get f / ( 0 ) = 0 ,
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[139]
i.e., −f ( x ) is differentiable, at x = 0 ex − 1
2
x2
Since, differentiability ⇒ continuity x
x
= lim ×
∴ f ( x ) ≤ x 2 , for all x ∈ R is continuous as well as x →0 x x 4
sin log 1 +
x K 4
differentiable at x = 0 . (b) .
K x x
K
1 4
x sin , x ≠ 0
18. f ( x ) = x and g ( x ) = xf ( x ) 2
x
2 e −1
0, x=0 x 4k
x
For f ( x ) = lim
x →0 x log 1 + x
1 sin
LHL = lim −h sin − k. 4
−
h →0 h x x
k 4
= 0 × a finite quantity between – 1 and 1 = 0
On applying limit we get
1
RHL = lim h sin = 0 4k = 12 ⇒ k = 3 (c)
h → 0+ h
20. Since g ( x ) is differentiable, it will be continuous at
Also, f ( 0 ) = 0 x=3
∴ lim g ( x ) = lim g ( x )
Thus LHL = RHL = f ( 0 )
x →3− x →3+
∴ f(x) is continuous at x = 0 2k = 3m + 2 …(i)
2 1 Also g ( x ) is differentiable at x = 0
x sin , x ≠ 0
g(x) = x
0, x=0 ∴ lim g / ( x ) = lim g / ( x )
x →3− x →3+
For g ( x )
k
=m
1 2 3 +1
LHL = lim −h 2 sin
−
h →0 h k = 4m …(ii)
2 Solving (i) and (ii), we get
= 0 × a finite quantity between – 1 and 1 = 0
1 2 8
RHL = lim h 2 sin = 0 m= ,k =
5 5
h → 0+ h
k+m = 2 (c)
Also, g ( 0 ) = 0
21.
∴ g ( x ) is continuous at x = 0 (b) 2x 2 2b 2 − 4b
19. Since f ( x ) is a continuous function therefore limit of a a x3
f ( x ) at x → 0 = value of f ( x ) at 0. 0 1 2
( ex − 1)
2
Continuity at x = 1
∴ lim f ( x ) = lim 2
x →0 x →0 x x =a⇒a=± 2
sin log 1 +
k 4 a
Continuity at x = 2
2b 2 − 4b
a=
2 2
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[140]
Put a = 2 2x
e − 1 − kx + x
= lim
2 = b 2 − 2b ⇒ b 2 − 2b − 2 = 0
(
x →0 ( x ) e 2x − 1
)
2 ± 4 + 4.2
b= = 1± 3
1 + 2x + ( 2x ) + ( 2x ) + ... − 1 − kx + x
2 3
2
2! 3!
So, ( a, b ) = ( 2,1 − 3 ) (c) = lim
x →0
x 1 + 2x + ( 2x ) + ( 2x ) + ... − 1
2 3
− x, x <1 ( ) 2! 3!
22. f ( x ) = −1
a + cos ( x + b ) , 1 ≤ x ≤ 2
4x 2 8x 3
f ( x ) is continuous (3 − k ) x + + + ...
= lim 2! 3!
x →0 2 4x 3 8x 3
⇒ lim f ( x ) = lim a + cos −1 ( x + b ) = f ( x ) 2x + + + ...
x →1− x →1+
2! 3!
⇒ −1 = a + cos −1 (1 + b )
For the limit to exist, power of x in the numerator
should be greater than or equal to the power of x in the
denominator. Therefore, coefficient of x in numerator is
cos −1 (1 + b ) = −1 − a …(a) equal to zero
⇒ 3−k = 0
f ( x ) is differentiable
⇒k=3
⇒ LHD = RHD So the limit reduces to
⇒ −1 =
−1 ( ) 4 8x
x2 +
2! 3!
+ ...
lim
1 − (1 + b )
2
x →0 2
( ) 4x 8x 2
x 2+ + + ...
2! 3!
⇒ 1 − (1 + b ) = 1 ⇒ b = −1
2
…(b)
4 8x
+ + ...
From (a) ⇒ cos −1 ( 0 ) = −1 − a = lim 2! 3! =1
x →0 4x 8x 2
π 2+ + + ...
∴ −1 − a = 2! 3!
2 Hence, f ( 0 ) = 1 (b)
π −π − 2 25. Since f(x) is continuous at x = 2
a = −1 − ⇒a= …(c)
2 2 ∴ lim f ( x ) = f ( 2 )
x →2
a π+2
∴ = (a) 1
b 2 ⇒ lim ( x − 1) x = k
x →2
2 −
(1∞ form )
π
23. lim f ( x ) = f ℓ
π 2 ∴e = k
x→
1 x−2
where ℓ = lim ( x − 1 − 1) ×
2
= lim
2 2 3 x →2 2 − x x →2 2 − x
⇒ k + = 1 ⇒ k = 1− ⇒ k = (c)
5 5 5 x−2
= lim
24. If the function is continuous at x = 0 , then lim f ( x ) x →2 x − 2
x →0 ⇒ k = e−1 (c)
will exist and f ( 0 ) = lim f ( x )
26. f ( x ) = x − π e − 1 sin x
x
x →0
1 k −1
Now, lim f ( x ) = lim − Check differentiability of f ( x ) at x = π and x = 0
x →0 x →0 x e2x − 1
at x = π
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[141]
π + h − π e
x +h
− 1 sin π + h − 0 ⇒ 4( λ − µ) = 0
RHD = lim
h →0 h ⇒ λ =µ
π − h − π e
x −h
− 1 sin π − h − 0 So, S ≡ ( λ, µ ) = {λ ∈ R & µ ∈ [0, ∞)}
LHD = lim =0
−h Therefore set S is subset of R × [0,∞) (a)
h →0
∵ RHD = LHD π
28. ∴ Function should be continuous at x =
Therefore, function is differentiable at x = π 4
π
at x = 0 ∴ lim f ( x ) = f
π 4
x→
4
h − π e − 1 sin h − 0
h
RHD = lim =0 − 2 cos x − 1
⇒ lim =k
h →0 h π cot x − 1
x→
4
−h − π e − 1 sin − h − 0
−h
− 2 sin x
RHD = lim =0 ⇒ lim = k (using L'Hospital rule)
π 2
h →0 −h x → − cosec x
4
∴ RHD = LHD
lim 2 sin 3 x = k
Therefore, function is differentiable. π
x→
4
at x = 0 .
3
1 1
Since, the function f ( x ) is differentiable at all the ⇒ k = 2 = (a)
2 2
points including π and 0.
x
29. f ( x ) = [ x ] −
i.e. f ( x ) is every where differentiable. 4
x
Therefore, there is no element in the set S. lim f ( x ) = lim [ x ] − = 4 − 1 = 3
⇒ S = φ (an empty set) (d) x → 4+ x →4 + 4
x
lim f ( x ) = lim [ x ] − = 3 − 0 = 3
= λ e − µ sin ( 2 t ) , t ∈ R
t
27. S = {( λ, µ ) ∈ R × R : f ( t ) x → 4− x → 4− 4
f (x) = 3
f ( t ) = λ e − µ sin ( 2 t )
t
∴ continuous at x = 4 (d)
a π − x + 1, x ≥ 5
30. f ( x ) =
=
(
λ e t − µ sin 2t, ) t>0 b π − x + 3, x > 5
( )
λ e − t − µ ( − sin 2t ) , t < 0
a π−5 +5 = b 5−π +3
a (5 − π) + 1 = b (5 − π) + 3
( ) ( )
λ e sin 2t + λ e − µ ( 2 cos 2t ) , t > 0
f / (x) =
t t ( a − b )( 5 − π ) = 2
( )
2
λ e − t sin 2t + λ e− t − µ ( −2 cos 2t ) , t < 0 a−b = (a)
5−π
− ( x + 1) , −1 ≤ x < 0
As, f ( t ) is differentiable
x , 0 ≤ x <1
∴ LHD = RHD at t = 0 31. f ( x ) = 2x , 1≤ x < 2
x+2
( )
⇒ λ .sin 2 ( 0 ) + λ e0 − µ 2 cos ( 0 )
x + 3
, 2≤x<3
, x=3
(
= λ e−0 .sin 2 ( 0 ) − 2 cos ( 0 ) λ e −0 − µ ) Function discontinuous at x = 0, 1, 3 (d)
⇒ 0 + ( λ − µ) 2 = 0 − 2( λ − µ)
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[142]
5 if x ≤1 1 1 1
a + bx if 1 < x < 3 = lim = = …(iii)
h →0 h + 1 + 1 1 + 1 2
32. f ( x ) =
b + 5x if 3 ≤ x < 5 Now, from equation (i),
30 if x≥5
If f ( x ) is continuous at x = 1 x ( ) ( )
f 0− = f ( 0 ) = f 0+ ⇒ p + 2 = q =
1
2
( ) ( )
∴ f (1) = f 1−1 = f 1+
⇒q=
1
and p =
−3
⇒5=a+b ...(i) 2 2
and if f ( x ) is continuous at x = 3 3 1
∴ ( p, q ) = − , (c)
∴ f ( 3) = lim f ( x ) 2 2
x →3
⇒ b + 5a = a + 3b ( )
34. f ( x ) = ln ( sin x ) , g ( x ) = sin −1 e− x
⇒ 4a = 2b
⇒ b = 2a ...(ii) ⇒ f ( g ( x ) ) = ln ( sin ( sin −1 e − x ) ) = − x
Also if f ( x ) is continuous at x = 5
⇒ f ( g ( x ) ) = −α
then lim f ( x ) = f ( 5 )
x →5
⇒ b + 25 = 30 ⇒ b = 5, a = 5 / 2 But given that ( fog )( α ) = b
Does not satisfy equation (i). Hence (D) is correct. (d)
∴ −α = b and f / ( g ( α ) ) = a, i.e., a = −1
sin ( p + 1) x + sin x , x<0 ∴ aα 2 − bα − a = −α 2 + α 2 − ( −1)
x
33. f ( x ) = q , x = 0 is continuous at ⇒ aα 2 − bα − a = 1 (b)
x + x2 − x g ( x ) − g (c)
, x>0 35. g / ( c ) = lim
x 3/ 2 x →c x −c
x=0 f ( x ) − f (c)
( )
Therefore, f 0− = f ( 0 ) = f 0+ ( ) …(i)
⇒ g / ( c ) = lim
x →c x −c
h + 1 −1 h +1 +1 h +1 −1 ∴ g ( x ) = f ( f ( x ) ) = 15 − 10 − 15 − 10 − x
= lim × = lim
h →0 h h + 1 + 1 h →0 h + 1 + 1 ( ) = 15 − 10 − x − 5
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[143]
∴ Then, the points where function g ( x ) is non- −1, −2 ≤ x < 0
39. f ( x ) =
2
differentiable are x − 1, 0 ≤ x ≤ 2
10 − x = 0 and 10 − x = 5 −1, −2 ≤ x < 0
Then, f ( x ) = 2
⇒ x = 10 and x − 10 = ±5 x − 1, 0 ≤ x ≤ 2
( )
37. Let g ( x ) = f f ( f ( x ) ) + ( f ( x ) )
2
1 + x 2 − 1, −2 ≤ x < 0
⇒ g (x) = 2
Differentiating both sides w.r.t. x, we get
( 2
)
x −1 + x −1 , 0 ≤ x ≤ 2
( )
g / ( x ) = f / f ( f ( x ) ) f / ( f ( x ) ) f / ( x ) + 2f ( x ) f / ( x )
2
x , −2 ≤ x < 0
( )
g / (1) = f / f ( f (1) ) f / ( f (1) ) f / (1) + 2f (1) f / (1)
= 0 , 0 ≤ x <1
= f / ( f (1) ) f / (1) f / (1) + 2f (1) f / (1) 2
(
2 x − 1
) , 1≤ x ≤ 2
= 3 × 3 × 3 + 2 × 1× 3 = 27 + 6 = 33 (a)
38. Since, f /
(x) = f (x)
( ) ( )
g / ( 0 ) = 0, g / 0+ = 0, g / 1− = 0, g / 1+ = 4 ( )
⇒ g ( x ) is not differentiable at x = 1
f / (x)
Then, =1
f (x) ⇒ g ( x ) is not differentiable at one point. (d)
⇒ ln f ( x ) = x + c loge ( loge x ) + x.
1
− 2x + 2y
dy
=0
x ⋅ loge x dx
f ( x ) = ±e x +c …(i)
1 dy
loge ( loge x ) + − 2x + 2y = 0 …(i)
Since, the given condition log e x dx
f (1) = 2
When x = e, y = 4 + e 2 . Put these values in (i),
From equation (i) f ( x ) = e x +c = ec e x dy
0 + 1 − 2e + 2 4 + e2 =0
dx
Then, f (1) = ec ⋅ e1
dy 2e − 1
c = (b)
⇒ 2 = e ⋅e dx 2 4 + e2
2
⇒ = ec 41. f ( x ) = sin x − x + 2 ( x − π ) cos x
e
There are two cases,
Then, from equation (i)
Case-1 x > 0
2 2
f ( x ) = ex ⇒ f / ( x ) = ex f ( x ) = sin x − x + 2 ( x − π ) cos x
e e
⇒ h / ( x ) = f / (f ( x )) ⋅ f / ( x ) f / ( x ) = 3cos x − 2 ( x − π ) sin x − 1
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[144]
f ( x ) = − sin x + x + 2 ( x − π ) cos x 1 1
x = 0, − ,
2 2
f / ( x ) = − cos x + 1 − 2 ( x − π ) sin x + 2 cos x
1 1
Then, K = − , 0,
f /
( x ) = cos x + 1 − 2 ( x − π ) sin x 2 2
Then, function f ( x ) is differentiable for all x < 0 Hence, K has exactly three elements. (c)
44. x ∈ ( −10, 10 )
Now check for x = 0
x
∈ ( −5, 5 ) → 9 integers
( )
f / 0+ RHD = 3 − 1 = 2 2
Check continuity at x = 0
f / ( 0− ) LHD = 1 + 1 = 2 f ( 0) = 0
f (0+ ) = 0 continuous at x = 0
LHD = RHD
f (0−1 ) = 0
Then, function f ( x ) is differentiable for x = 0 . So it is
Function will be discontinuous when
differentiable everywhere x
= ± 4, ± 3, ± 2, ± 1
Hence, k = φ (a) 2
8 point s of discontinuity. (8)
max x , x 2
42. Given f ( x ) =
{ } x ≤2
ae x + be − x , −1 ≤ x < 1
8 − 2 x , 2< x ≤4
y 45. f ( x ) = cx 2 , 1≤ x ≤ 3
2
y = x y = x2
2
ax + 2cx , 3 < x ≤ 4
y=8–2|x| y=8–2|x|
y = |x| y = |x| For continuity at x = 1
lim f ( x ) = lim f ( x )
x →1− x →1+
x
−1
-4 -2 -1 1 2 4 ⇒ ae + be = c ⇒ b = ce − ae2 …(i)
For continuity at x = 3
lim f ( x ) = lim f ( x )
∵ f ( x ) is not differentiable at −2, −1, 0 and 2 .
x →3− x →3+
∴ S = {−2, −1, 0,1, 2} (b) ⇒ 9c = 9a + 6c ⇒ c = 3a …(ii)
f /
(0) + f ( 2) = e
/
43. Consider the function
{
f ( x ) = max − x , − 1 − x 2 } ( aex − bex )x =0 + ( 2cx )x=2 = e
⇒ a − b + 4c = e …(iii)
Now, the graph of the function From (i), (ii) and (iii)
y a − 3ae + ae2 + 12a = e
(
⇒ a e2 + 13 − 3e = e )
e
O x ⇒a= (d)
e2 − 3e + 13
4 4 4
46. A = lim x = lim x − x = 4
x →0 x x →0 x x
x x 1
1 f ( x ) = x 2 sin ( πx ) will be discontinuous at non-
2 2
integers
at
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[145]
ℓn (1 + 3x ) ℓn (1 − 2x ) f / ( 5) − f / ( 2)
47. k = lim − ⇒ ≥ 4 ⇒ f / ( 5 ) ≥ 12 + f / ( 2 )
x →0 x x 5−2
k = 3+ 2 = 5 (5)
48. ⇒ f / ( 5 ) ≥ 17
Hence, f ( 5 ) + f / ( 5 ) ≥ 28 (b)
y = x2 y=x 2
y=x
51. f ( x + y ) = f ( x ) + f ( y ) + xy2 + x 2 y
Differentiate w.r.t. x
(0,0) (1,0)
f / ( x + y ) = f / ( x ) + 0 + y2 + 2xy
{ }
f ( x ) = max . x, x 2
Put y = − x
f / ( 0 ) = f / ( x ) + x 2 − 2x 2 …(i)
x 2 , x<0
f (x)
⇒ f (x) = x , 0 ≤ x <1 ∵ lim = 1 ⇒ f (0) = 0
2 x →0 x
x , x ≥1
∴ f / (0) = 1 …(ii)
∴ f ( x ) is not differentiable at x = 0,1 (a)
From equations (i) and (ii),
49. f ( x ) is differentiable then, f ( x ) is also continuous.
∴ lim f ( x ) = lim f ( x ) = f ( π ) ( )
f / ( x ) = x 2 + 1 ⇒ f / ( 3) = 10 (10)
x →π+ x →π−
−x − 1
⇒ −1 = −K 2 ⇒ K 2 = 1 , x < −1
2
2K ( x − π ) , x ≤ π π
∴f / (x) = 1 52. f ( x ) = + tan −1 x , −1 ≤ x ≤ 1
−K 2 sin x x > π 4
1
lim f ( x ) = lim f ( x ) 2 ( x − 1) , x >1
Then,
x →π+ x →π− y
2K1 , x≤π π
+ tan −1 x
f // ( x ) = x −1
− K 2 cos x, x > π 1 4
− ( x + 1) 2
2
Then, lim f ( x ) = lim f ( x ) x
x →π+ x →π− (-1,0) (0,0) (1,0)
1
⇒ 2K1 = K 2 ⇒ K1 =
2
It is clear from above graph that,
1
So, ( K1 , K 2 ) = ,1 (a) f ( x ) is discontinuous at x = 1 .
2
50. Let f be twice differentiable function i.e. continuous on R − {1}
∵f / (x) ≥ 1 f ( x ) is non-differentiable at x = −1,1
f ( 5) − f ( 2)
⇒ ≥1 i.e. differentiable on R − {−1,1} . (a)
3
sin ( a + 2 ) x + sin x
⇒ f (5) ≥ 3 + f ( 2) 53. LHL = lim
x →0 x
⇒ f ( 5) ≥ 3 + 8 ⇒ f ( 5 ) ≥ 11 sin ( a + 2 ) x sin x
= lim ( a + 2 ) + lim = a +3
x →0 ( a + 2 ) x x →0 x
and also f // ( x ) ≥ 4
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m
[146]
f (0) = b 1
f / ( b) = (a)
5
(1 + 3h )1/ 3 − 1
RHL = lim =1 55. For a constant function f ( x ) , option (a), (c) and (d)
h →0 h
doesn’t hold and by LMVT theorem, option (b) is
incorrect. (bonus)
∵ Function f ( x ) is continuous 56. From LMVT for x ∈ [ −7, −1]
∴ lim f ( x ) = lim f ( x ) = f ( 0 ) f ( −1) − f ( −7 ) f ( −1) + 3
≤2⇒ ≤ 2 ⇒ f ( −1) ≤ 9
x →0 − x →0 + ( −1 + 7 ) 6
∴ a + 3 = 1 ⇒ a = −2
From, LMVT for x ∈ [ −7, 0]
and b = 1
f ( 0 ) − f ( −7 )
Hence, a + 2b = 0 (c) ≤2
(0 + 7)
54. It is given that functions f and g are differentiable and
fog is identity function. f (0) + 3
≤ 2 ⇒ f ( 0 ) ≤ 11
∴ ( fog )( x ) = x ⇒ f ( g ( x ) ) = x 7
f / ( g ( a )) ⋅ g / ( a ) = 1 ∑ f ( f ( x ) ) = f ( f (1) ) + f ( f ( 3) ) + f ( f ( 5) )
= 1+1+1 = 3 (3)
f / (b) ⋅5 = 1
C A T J E E , R a m a n N i w a s , N e a r A k a s h v a n i , M e h mo o r g a n j , V a r a n a s i , P h : ( 0 5 4 2 ) 2 3 6 3 4 5 5 . we b s i t e : c a t j e e . c o m